2021
DOI: 10.3389/fpubh.2021.661615
|View full text |Cite
|
Sign up to set email alerts
|

Exploring Feasibility of Multivariate Deep Learning Models in Predicting COVID-19 Epidemic

Abstract: Background: Mathematical models are powerful tools to study COVID-19. However, one fundamental challenge in current modeling approaches is the lack of accurate and comprehensive data. Complex epidemiological systems such as COVID-19 are especially challenging to the commonly used mechanistic model when our understanding of this pandemic rapidly refreshes.Objective: We aim to develop a data-driven workflow to extract, process, and develop deep learning (DL) methods to model the COVID-19 epidemic. We provide an … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(8 citation statements)
references
References 17 publications
0
8
0
Order By: Relevance
“…To date, many studies have been conducted on COVID-19 transmission to effectively contain its spread. Representative infection transmission models, such as the susceptible–infected–removed model [ 3 , 4 , 5 , 6 , 7 ] and data-driven time series [ 8 , 9 ], are macroscopic models. These models have the advantage of including macro-parameters and data.…”
Section: Introductionmentioning
confidence: 99%
“…To date, many studies have been conducted on COVID-19 transmission to effectively contain its spread. Representative infection transmission models, such as the susceptible–infected–removed model [ 3 , 4 , 5 , 6 , 7 ] and data-driven time series [ 8 , 9 ], are macroscopic models. These models have the advantage of including macro-parameters and data.…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, ConvLSTM achieved the best results in a comparative study against 5 other models using data from 8 different countries over the period Jan 22 - Sep 6, 2020 and achieved MAPE in the range 0.628 - 6.021 [18] . Other LSTM variants such as multivariate LSTM and encoder-decoder LSTM have also shown promising results [15] . A summary of the current studies is provided in Table 5 .…”
Section: Deep Learning Models For Covid-19 Forecastingmentioning
confidence: 99%
“… Study Methodology Data MAPE Chandra et al, 2022 [14] Compared LSTM and its variants in 2-month ahead forecasting of cases in India and found that ED-LSTM achieves the lowest error. India; Apr 2020 - Sep, 2021 Chen et al, 2021 [15] Used M-LSTM with 10 input variables. The mutivariate model was shown to perform better than the individual univariate models.…”
Section: Deep Learning Models For Covid-19 Forecastingmentioning
confidence: 99%
“…Specifically, the family of deep recurrent neural networks have proven to be an attractive approach for epidemic forecast 56 due to their acute capability to learn time series. Among these methods, uni-variate 57 and multi-variate 58 , 59 LSTM models have been successful at predicting influenza and COVID-19, mainly due to their capability to memorize long-term dependencies. DeepGLEAM 60 uses a stochastic Diffusion Convolutional RNN (DCRNN) model, which considers short (commuting) and long range (air flight) mobility network connections, to forecast COVID-19 deaths at county and state granularities.…”
Section: Literature Reviewmentioning
confidence: 99%